Dificulties and solutions to improve second year part-time students' English speaking skill at University of Languages and International studies-Vietnam National University - Nguyen, Thi Nguyet Thu (ĐHNN, 2017)
The research in this minor thesis is carried out to investigate the current situation of learning English speaking skill of second year part-time students of English, at A2 campus University of Languages and International Studies -VNU. However, this study only focuses on difficulties experienced by the students of English and some recommendations including strategies and classroom techniques and activities for both teachers and students to minimize those difficulties. Especially, this research attempts to explore the potential sources causing .The difficulties of students in learning speaking English and at the same time identify the specific problems of those causes respectively. Moreover, some recommendations are made with the aim to help students in this university to improve the quality of learning the speaking skill